2018
DOI: 10.1038/s41598-018-29893-7
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: The molecular chaperones DNAJB6 and Hsp70 cooperate to suppress α-synuclein aggregation

Abstract: The Article mentions but does not include control data demonstrating that a random mutation in the cDNA sequence of DNAJB6b used in the study does not affect the behaviour of its protein product. Specifically, the cDNA sequence of DNAJB6b WT and DNAJB6b H31Q in the plasmids used for all the experiments reported in this study contained a mutation (TTC to TCC) leading to the F46S mutation in the translated proteins, which was randomly introduced during the cloning. The mutation did not change the localisation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Chaperones and co-chaperones are essential players in the regulation of cellular proteostasis; in particular, they protect cells from pathogenic aggregation of misfolded proteins [ 34 ]. For instance, it has been shown that, in vitro, HSP70 alone or in cooperation with different chaperones/co-chaperones inhibits formation of α-synuclein fibrils [ 35 , 36 ] and tau aggregates [ 32 ], and reduces polyglutamine (polyQ)-induced toxicity when exogenously added to cultured cells [ 37 ]. Other chaperones such as HSP60 and HSP40 have been shown to suppress α-synuclein fibrillization in vitro and to block the polyQ-induced toxicity, respectively [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chaperones and co-chaperones are essential players in the regulation of cellular proteostasis; in particular, they protect cells from pathogenic aggregation of misfolded proteins [ 34 ]. For instance, it has been shown that, in vitro, HSP70 alone or in cooperation with different chaperones/co-chaperones inhibits formation of α-synuclein fibrils [ 35 , 36 ] and tau aggregates [ 32 ], and reduces polyglutamine (polyQ)-induced toxicity when exogenously added to cultured cells [ 37 ]. Other chaperones such as HSP60 and HSP40 have been shown to suppress α-synuclein fibrillization in vitro and to block the polyQ-induced toxicity, respectively [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%